Pascal trapezoids emerging from hypercomplex polynomial sequences - Cação, Isabel (2018)
The construction of two different representations of special Appell polynomials in (n+1) real variables with values in a Clifford algebra suggested to explore the relation between the respective coefficients. Properties of sequences resulting from such relation and an interesting trapezoidal array of their elements are pointed out.